Relationships among cyberbullying, parental attitudes, self-harm and suicidal behavior among adolescents: results from a school-based survey in Vietnam - Hoang Thuy Linh Nguyen; Keiko Nakamura; Kaoruko Seino; Van Thang Vo (BMC, 2020)
Abstract Background The rapid and widespread development of social networking sites has created a venue for an increase in cyberbullying among adolescents. Protective mechanisms and actions must be considered, such as how proximal family factors can prevent self-harm and suicidal behaviors among adolescents exposed to cyberbullying. The present study examined the associations among cyberbullying, parental attitudes, self-harm, and suicidal behaviors after adjusting for confounding factors. Methods Data were obtained from a school-based survey of randomly selected grade 6 students (11 years old) performed in Hue City, Vietnam, in 2018. A total of 648 students were interviewed face-to-face using a structured questionnaire based on the Global School-based Student Health Survey (GSHS). Univariate, multivariable logistic regression analyses were performed at 95% confidence level. Results After adjusting for gender, perceived academic pressure, unhealthy behaviors, use of Internet devices, school bullying, and family living situation, a significantly higher risk of self-harm was detected among those who had experienced cyberbullying (adjusted odd ratio [AOR] = 2.97; 95% CI, 1.32-6.71). Parental acceptance retained a significant association with self-harm and suicidal behavior (P < 0.05) while parental concentration did not exhibit a significant association in a multivariable logistic regression model. In addition, suicidal ideation and suicidal planning were associated with an interaction effect between cyberbullying and parental concentration (AOR = 0.37; 95% CI, 0.15-0.94 and AOR = 0.23; 95% CI, 0.06-0.87, respectively). Conclusion Cyberbullying has become an important phenomenon associated with self-harm among young adolescents in developing countries, and parental acceptance in proxy of parental attitude was positively related with severe mental health issues among adolescents. Thus, sufficient attention in efforts to promote adolescent health should be focused on family factors in the digital era of developing countries.